Interpretation of Cigarette Wrap Design and Smoker Response from the Perspective of Visual Communication - Muhammad Ridholi; Ahmad Tamrin Sikumbang (PERSPEKTIF, 2026)
Cigarette packaging has evolved beyond its protective function into a strategic medium of visual communication that conveys symbolic messages through colors, typography, logos, and other visual elements. This study aims to analyze smokers’ interpretations of cigarette wrapper designs and examine their responses from the perspective of visual communication. A qualitative approach with a narrative design was employed. The research was conducted at Cafe Masa Moeda, Medan, involving ten active smokers who regularly consumed Marlboro Filter Black and Sampoerna A Mild cigarettes. Data were collected through structured interviews, direct observations, and visual documentation, and analyzed using data reduction, data display, and conclusion drawing supported by triangulation techniques. The findings reveal that smokers construct different meanings from the visual elements of cigarette packaging. Marlboro Filter Black is predominantly interpreted as representing masculinity, firmness, elegance, and premium quality through its dominant black color, whereas Sampoerna A Mild is perceived as clean, modern, light, and relaxed through its white-red color combination. Smokers’ responses are reflected in cognitive, affective, and conative dimensions. While the packaging effectively enhances brand recognition and evokes emotional impressions, its influence on purchasing behavior remains limited, as taste, habitual consumption, and personal preferences are more decisive factors. The study concludes that cigarette wrapper design functions as an effective medium of visual communication in shaping brand image and social identity, although it has limited capacity to influence smoking behavior directly.